Fair price comparison in the WTO anti-dumping agreement : recent WTO panel decisions against the zeroing method - Jong, Bum Kim (2002)
Interprets the dumping margin calculation provisions of the WTO Anti-dumping Agreement by first studying the amendment of the GATT Anti-dumping Code through the Uruguay Round negotiations. Discusses the GATT disputes involving margin calculation issues and compares them with the analogous WTO disputes. Provides a statistical interpretation of the price comparison provisions of the WTO anti-dumping Agreement in the context of the recent rulings in the WTO disputes. Concludes with suggestions for future amendment to the WTO anti-dumping Agreement with a view to providing a better foundation for fair price comparison.